Robust Control of Continuum Robots using Interval Arithmetic. Issue 1 (July 2017) - Hisch, Florian; Giusti, Andrea; Althoff, Matthias
Abstract: We consider the problem of controlling pneumatically actuated continuum robots with uncertain system dynamics and input disturbance. While such systems are intrinsically structurally safe due to soft and light-weight components, their structural flexibility challenges the control stability and performance. We present a robust tracking control approach using interval arithmetic. With this approach a user defined tracking performance can be ultimately met without the need for empirical estimation of bounds of perturbations from model uncertainty and input disturbances. We show the validity of our approach by simulating scenarios with different parametric uncertainty and by comparing the performance with an existing inverse-dynamics controller.